Associação do perfil biofísico fetal e gasometria de cordão umbilical em partos cesáreos eletivos em pacientes sem trabalho de parto - Alim Alves Demian (1999)
Purpose: The cord blood gas values is the best way to avaliable fetal well done, but this method have a high risk of lesions or infection, and have a high difficult degree to obtanied. US show a window no-invasive of uterine cavity, and a fetal biophysical profile Manning it is one. That assocition will show us a relationship between fetal biphysicalprofile and cord blood gas in patients undergoing cesarean section before the onset of labor. Objetive: Relationship between fetal biphysical profile and cord blood gas in patients undergoing cesarean section before the onset of labor. Material and methods: 1996 january at 1998 november women (104) has a singleton high-risk pregnancy wereinclunding in study. The age was 18 and 43 years old, and gestacional age 28 at 41 weeks FBP was realize at 4 hours before cesarean section and non-stress test after the US examination. After the baby was born the sampling cord blood was do and went for de hospital laboratory own. We use a qui test and a Fisher exact test whem necessary. The EPI INFO 1996 version program was done in statistic study. P value < 0,05 was a significative test. Results: 42,31% FBP was altered, in this fetal blood gas we found tree variables altered (pH < 7,20 p 0,004; pCO2 > 40mmHg p 0,01; BE 12 p 0,02) but, pO2 was normal. Coclusion: The FBP score 8 and 10 show a fetal well done. Score 6 or below show us a fetal compromissed well done (acidosis and hypercapnia). pO2 was normal in our study, however, pH, pCO2 and BE give us a compromissed new born. The relationship between fetal biphysical profile and cord blood gas in patients undergoing cesarean section before the onset of labor show us how a important way to avaliabe fetal well done.